Analysis of Teacher-Student Communication in Enhancing Learning Motivation - Mila Sari Dewi; Agus Maryanto (Departement of Mathematics Education, 2024)
This article describes the role of teachers as motivators in enhancing student learning motivation, including in Islamic religious education. The study is qualitative with a descriptive approach aimed at uncovering facts and providing interpretation. The results show that teachers increase learning motivation through three communication methods: lecturing, acting as moderators, and managing group work. However, there are several problems faced by teachers, such as a lack of learning media and monotonous methods, which make students easily bored. Students also face challenges such as fear and shyness in asking questions, as well as a lack of concentration. A family environment that lacks care also affects students' studies. Factors that support learning motivation include the characteristics of inspirational teachers, facilities like school mosques, and the diversity of student characters. Meanwhile, obstacles include a shortage of educators, Islamic religious education schedules at the end of the day, and divided student attention.Bagian Atas Formulir